School Social Worker Voice during COVID-19 School Disruptions: A National Qualitative Analysis. Issue 2 (25th May 2021) - Capp, Gordon; Watson, Kate; Astor, Ron A; Kelly, Michael S; Benbenishty, Rami
Abstract: The novel coronavirus (COVID-19) pandemic has created unprecedented impacts on our schools and society, requiring school social workers (SSWs) to attend to layered and cascading effects for students and their families. This study presents rich qualitative data from a national survey of SSWs about their personal and professional roles supporting students, families, and staff members as schools shifted to remote instruction. Findings indicate that SSWs are highly concerned about a lack of basic needs resources, including food, housing, and mental health support for students and families. SSWs highlighted the unequal effects of school closures for families without technology and Internet access as well as the difficulties providing services during the pandemic. Recovery policies should target resources to schools with the highest needs while prioritizing food, housing, mental health, and access to tools for online learning. SSWs also need additional and refined professional support to overcome their isolated roles in schools and bolster their ability to deliver online services effectively.